Pengaruh Ekstrak Biji Pala (Myristica fragrans) Terhadap Jumlah Eritrosit dan Leukosit pada Tikus Putih (Rattus norvegicus) - -, Linda -; Ramadhan, Achmad -; Tureni, Dewi - (e-JIP BIOL, 2014)
Abstract The number of erythrocytes and leukocytes are very important parameter to assess the health, which viewed from both their respective functions are essential for the body. Erythrocytes has a function to transport O2 to the whole body and leukocyte maintains the body defense. This study aimed to observe the effect of the seed extract of nutmeg (Myristica fragrans) on the number of erythrocytes and leukocytes, and to determine the best concentration in maintaining the number of erythrocytes and leukocytes. This research was conducted in the Laboratory of Biology of Faculty of Teacher Training and Education and Laboratory of Pharmacy Faculty of Matematics and Natural Sciences of University of Tadulako and Health Labolatory of Central Sulawesi. This research was an experimental methodÂ  through Completely Randomized Design (CRD), consisted of 6 treatments and 3 replications. Treatment K1 was a control group who was not given the extract, treatment K2, K3, respectively 1%, 2% was given the nutmeg seed extract 1 ml/day, treatment K4, K5, K6, respectively 4%, 8%, 16 % given the nutmeg seed extract 0.5 ml/day. The datas were analyzed using ANAVA analysis were processed with the software Statistics 27, then followed by LSD test. The results showed that the extract of nutmeg (Myristica fragrans) with 5 different concentrations didnâ€™t have a significant influence to the number of erythrocytes and leukocytes in rats (Rattus norvegicus) when compared to the control group. Keywords: Extract, Myristica fragrans, erythrocytes, leukocytes, Rattus norvegicus Abstrak Jumlah eritrosit dan leukosit merupakan dua parameter yang sangat penting untuk menilai kesehatan, dimana bila dilihat dari kedua fungsinya masing-masing sangat penting bagi tubuh. Eritrosit berfungsi untuk mengangkut O2 keseluruh tubuh dan leukosit berfungsi untuk menjaga pertahanan tubuh. Penelitian ini bertujuan untuk mengamati pengaruh ekstrak biji pala (Myristica fragrans) terhadap jumlah eritrosit dan leukosit, dan menentukan konsentrasi yang terbaik dalam mempertahankan jumlah eritrosit dan leukosit. Penelitian ini dilakukan di Laboratorium Biologi Fakultas Keguruan dan Ilmu Pendidikan, Laboratorium Farmasi Fakultas MIPA Universitas Tadulako dan Laboratorium Kesehatan Provinsi Sulawesi Tengah. Metode penelitian yang digunakan adalah metode eksperimen dengan pola Rancangan Acak Lengkap (RAL), yang terdiri dari 6 perlakuan dan 3 kali ulangan. Perlakuan K1 merupakan kelompok kontrol yang tidak diberi ekstrak, perlakuan K2, K3, masing-masing 1%, 2% diberi ekstrak biji pala sebanyak 1 ml/hari, perlakuan K4, K5, K6, masing-masing 4%, 8%, 16% diberi ekstrak biji pala sebanyak 0,5 ml/hari. Data yang diperoleh dianalisis dengan menggunakan analisis ANAVA yang diolah dengan software Statistik 27, dilanjutkan dengan uji BNT. Hasil penelitian menunjukkan bahwa pemberian ekstrak biji pala (Myristica fragrans) dengan 5 konsentrasi berbeda tidak memberikan pengaruh yang signifikan terhadap jumlah eritrosit dan leukosit pada tikus putih (Rattus norvegicus) jika dibandingkan dengan kelompok kontrol. Kata Kunci: Ekstrak, Myristica fragrans, eritrosit, leukosit, Rattus Norvegicus